2021
DOI: 10.5812/ijpbs.114376
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of General Emotion Questionnaire-Contrast Avoidance Model

Abstract: Background: According to Contrast Avoidance Model, those suffering from generalized anxiety disorder (GAD) are afraid of severe emotional changes such as the transition from a good or neutral position to sudden unhappiness following a negative event. Also, the model shows that persistent worrying can be used to maintain negative emotions as a means of preventing a sudden change to negative in people with GAD. Objectives: This study aimed to evaluate the psychometric properties of the Persian version of the Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To date, two studies examining the original and translated versions of the CAQ-GE have found a significant and strong correlation between CAQ-GE and GAD (r = .80) and CAQ-GE and MDD (r = .63) symptoms (Javaherirenani et al, 2021;White et al, 2021), providing preliminary evidence for the relevance of CAM across GAD and MDD. An additional study examined the sensitivity and specificity of the CAQ-GE in predicting GAD and found a sensitivity of 89.7 and a specificity of 89.3 accounting for an area under the curve of 96% (Llera & Newman, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, two studies examining the original and translated versions of the CAQ-GE have found a significant and strong correlation between CAQ-GE and GAD (r = .80) and CAQ-GE and MDD (r = .63) symptoms (Javaherirenani et al, 2021;White et al, 2021), providing preliminary evidence for the relevance of CAM across GAD and MDD. An additional study examined the sensitivity and specificity of the CAQ-GE in predicting GAD and found a sensitivity of 89.7 and a specificity of 89.3 accounting for an area under the curve of 96% (Llera & Newman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported good psychometric properties of the CAQ-GE (Javaherirenani et al, 2021;Llera & Newman, 2017;Rogers et al, 2022;White et al, 2021). Thus, the CAQ-GE was used to examine whether CAM might be a common construct within the three disorders.…”
Section: Introductionmentioning
confidence: 99%